Cryoablation in the treatment of early breast cancer: a comprehensive analysis - Xing, Yanli; Li, Hongmei; Yuan, Ting; Zou, Xiaojiao; Liang, Bing; Ma, Yangyang; Niu, Lizhi (Frontiers in Oncology, 2025)
Cryoablation has emerged as a promising local treatment technique for early breast cancer, garnering significant interest in recent years. This review delves into the fundamental principles of cryoablation, its clinical applications, efficacy assessments, and comparisons with traditional treatment modalities. We explore the potential advantages and challenges associated with incorporating cryoablation into the management of early breast cancer. Furthermore, we analyze current research developments and future directions in this field, aiming to provide valuable insights for clinical practice and enhance patient care in breast cancer management.